Da Casa de Detenção à Casa da Cultura de Pernambuco (1963-1982). - Silva, Josevane Francisco da (2020)
In this dissertation, we tried to analyze the creation of the House of Culture of Pernambuco from two approaches: first, taking it as the object of a broader political, socio-cultural and economic project in the State of Pernambuco; second, shedding light on the process of reframing the use of the site. Our time frame is from the period between 1963 and 1982. As a starting point, we discuss the embryonic stage, that is, the idealization of this cultural apparatus verified in the 1960s and its subsequent interruption with the 1964 civil-military coup of the penitentiary activities carried out between 1971 and 1973, as well as the restructuring of the building and the implementation of new equipment aiming at the inauguration, which took place in 1976. Finally, we reflect on the government effort that took place since the first years, with the intention of transforming the House of Culture- today House of Culture Luiz Gonzaga - in a center of reference for the cultural manifestations of the State, aiming at the development of tourism through the valorization of the intangible heritage of Pernambuco.